Career Self:: A Longitudinal Study with College Students - Silva, Ana Daniela (2011)
The career self constitutes an organized subset of the person’s cognitive universe, responsible for the subjective character that the person attributes to career. This study aims to evaluate changes in the content of the career self of college students, from the beginning to the end of last year’s graduation. Therefore, we used repeated measurements of the indices of the Career Repertory Grid (Silva & Taveira, 2005; Silva, 2008). Eighty students participated in this study, 49 women (61.25%) and 31 men (38.75%), aged between 21 and 45 years (M = 23.9, SD = 4.31). The results indicate that at the end of graduation students decrease the distance they build towards others and maintain a positive construction of the career self.